Characterizing Medicare Reimbursements and Clinical Activity Among Female Otolaryngologists. (July 2022) - Panth, Neelima; Torabi, Sina J.; Kasle, David A.; Savoca, Emily L.; Zogg, Cheryl K.; O'Brien, Erin K.; Manes, R. Peter
Objective: To evaluate geographic and temporal trends in Medicare fee-for-service (FFS) billing and reimbursements across female otolaryngologists (ORL). Methods: We performed a cross-sectional, retrospective analysis of the 2017 Medicare Physician and Other Suppliers Aggregate File. We analyzed differences in the number of services, patients, reimbursements, unique Current Procedural Terminology (CPT) codes used, and services billed per patient among female ORLs. Results: Female ORLs accounted for 15.2% of the 8453 Medicare-reimbursed ORLs. Female ORLs who graduated between 2000 and 2010 were reimbursed a median of 58 031.9 (IQR: 32 286.5-91 512.2) and performed a median of 702 (IQR: 359.5-1221.5) services, significantly less than those who graduated between 1990 and 1999 (median: 67 508.9; IQR: 37 018.0-110 471.5; P < .001; median: 1055.5; IQR: 497.3-1944; P < .001). Female ORLs who graduated between 2000 and 2010 saw a median of 232 patients (IQR: 130.5-368), significantly less than those who graduated between 1990 and 1999 (median: 308; IQR: 168.3-496; P < .001) patients, significantly more than those. Female ORLs in urban settings performed a median of 795 (IQR: 364-1494.3) services and billed for a median of 42 (IQR: 28-58) unique codes, significantly fewer than their counterparts in rural settings (median: 1096; IQR: 600-2192.5; P = .002; median: 54; IQR: 31.5-64.5; P = .001). Conclusions: Medicare reimbursements and billing patterns across female ORLs varied by graduation decade and geography. Female ORLs further along in their careers may be reimbursed more with greater clinical volume and productivity. Those practicing in urban settings may have practices with decreased procedural diversity and lower clinical volume compared to their counterparts in rural areas.